2012
DOI: 10.5898/jhri.1.1.riek
|View full text |Cite
|
Sign up to set email alerts
|

Wizard of Oz Studies in HRI: A Systematic Review and New Reporting Guidelines

Abstract: Many researchers use Wizard of Oz (WoZ) as an experimental technique, but there are methodological concerns over its use, and no comprehensive criteria on how to best employ it. We systematically review 54 WoZ experiments published in the primary HRI publication venues from 2001-2011. Using criteria proposed by Fraser and Gilbert (1991), Green et al. (2004), Steinfeld et al. (2009), and Kelley (1984), we analyzed how researchers conducted HRI WoZ experiments. Researchers mainly used WoZ for verbal (72.2%) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
206
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 518 publications
(237 citation statements)
references
References 74 publications
2
206
0
2
Order By: Relevance
“…We may think of teleoperation as deception and as an ethical concern-i.e., that by not telling a person up front that a robot is teleoperated, they are being deceived into acting a particular way and treating the robot a particular way [1], [9]. However, throughout scientific research, we deceive participants in research studies.…”
Section: Research Questionsmentioning
confidence: 99%
See 1 more Smart Citation
“…We may think of teleoperation as deception and as an ethical concern-i.e., that by not telling a person up front that a robot is teleoperated, they are being deceived into acting a particular way and treating the robot a particular way [1], [9]. However, throughout scientific research, we deceive participants in research studies.…”
Section: Research Questionsmentioning
confidence: 99%
“…Teleoperation or Wizard-of-Oz (WoZ) control of social robots is a pervasive method used in empirical studies of human-robot interaction (HRI) [1]. Using WoZ control is usually framed as a way to study human behavior with a robotic system that behaves in certain ways before it is potentially possible to build the system in actuality (usually due to technological challenges that have yet to be surmounted).…”
Section: Introductionmentioning
confidence: 99%
“…Previous guidelines highlight the importance of scenario constraints for WoZ experiments. (Dahlbäck et al 1993;Fraser and Gilbert 1991;Green et al 2004;Riek 2012). The scenario constraints allow participants to have a task to solve that requires the use of the system, and where there is not a single way to solve the problem (Riek 2012;Dahlbäck et al 1993).…”
Section: Wizard Of Ozmentioning
confidence: 99%
“…Finally, the WoZ allows an iterative design approach for building user interfaces as it is easy to use, requires little programming and supports rapid testing and interfaces modifications (Klemmer et al 2000). The design of a WoZ experiment may contain different amounts of control ranging from a complete automation of the interaction to an interaction solely dependent on the wizard, as well as mixed-initiative interactions (Riek 2012). Green, Huttenrauch, and Eklundh (2004) set one of the most recognized conditions for conducting a WoZ experiment: the user should have access to specific instructions, the designers should have a behavior hypothesis as well as a specified robot behavior.…”
Section: Wizard Of Ozmentioning
confidence: 99%
“…Dahlbäck, Jönsson, and Ahrenberg (1993) showed that this paradigm is suitable when high-quality empirical data is required but gathering the data is not a simple task. When designing a WoZ experiment, it is important to consider the role of the wizard and ensure that this role is properly controlled for (Riek, 2012).…”
Section: Wizard Of Ozmentioning
confidence: 99%